Relações étnico-raciais na Educação em Química a partir da Pedagogia Histórico-Crítica - Mendes, Carolina Borghi [UNESP]; Massi, Luciana [UNESP]; Colturato, Andriel Rodrigo [UNESP]; Stachowski, Lucas Nakamura [UNESP] (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (UNESP), Faculdade de Ciências, campus de Bauru., 2025)
Teaching African, Afro-Brazilian and Indigenous history and culture has been mandatory in Brazil for more than two decades. Although publications in the field of chemistry education offer didactic proposals, they lack a clear pedagogical foundation on how to incorporate ethnic-racial relations. This research is theoretical and conceptual, rooted in historical-critical pedagogy and historical-dialectical materialism. It seeks to provide a foundation for integrating racial-ethnic relations into chemistry education, considering the connections between these issues and scientific concepts. We begin with a historical-critical bibliography in dialogue with ethnic-racial relations, mobilizing categories such as mediation, singular-particular-universal, humanization, alienation, and generic objectification. In terms of social practice, we defend a teaching that is not reduced to the chemical concept, nor a contextualization without concreteness, since chemical contents are syntheses of multiple determinations and contradictions between the economic system and traditional communities in historical processes of humanization and alienation of science.

A obrigatoriedade do ensino de história e cultura africana, afro-brasileira e indígena se impõe há mais de vinte anos. Ainda que publicações da área de Educação em Química avancem com propostas didáticas, a forma como inserem as relações étnico-raciais prescinde de fundamentação pedagógica clara. Esta pesquisa, de natureza teórico-conceitual, está alicerçada na Pedagogia Histórico-Crítica e no Materialismo Histórico-Dialético e tem como objetivo apontar fundamentos para a inserção da Educação das Relações Étnico-Raciais na Educação em Química de forma concreta, considerando uma efetiva relação entre a questão étnico-racial e os conceitos científicos. Partimos de um acervo histórico-crítico em diálogo com as relações étnico-raciais, mobilizando categorias como mediação, singular-particular-universal, humanização, alienação e objetivações genéricas. Referenciados na prática social, defendemos um ensino não reduzido ao conceito químico, tampouco à contextualização sem concretude, visto que conteúdos químicos são sínteses de múltiplas determinações e contradições entre sistema econômico e comunidades tradicionais em meio aos processos históricos de humanização e alienação da ciência.
Ethnic-racial relations in chemistry education from a historical-critical pedagogy
Keywords: Chemistry teaching; Historical-critical pedagogy; Scientific concept; Historical and dialectical materialism; Ensino de química; Pedagogia histórico-crítica; Conceito científico; Materialismo histórico e dialético